A Declining Trend of 'Leishmaniasis' Based on Previous Data in Larstan, South of Iran 2007-2017 - Ahmad Abolghazi; Forough Ebrahimizadeh; Fatemh Sharafi; Naser Hatami; Zahra Vafai (Ubiquity Press, 2019)
Introduction: 'Cutaneous Leishmaniasis' is a unicellular of the Leishmania type, and 0.7 to 1.2 million people are annually infected by 'Cutaneous Leishmaniasis'. Larestan is one of the southern cities of Fars Province. Every year, some issues of 'Cutaneous Leishmaniasis' are reported from Larestan. This study aims to analyze the prevalence of 'Cutaneous Leishmaniasis' in Larestan from 2007 to 2017. Methodology: The present study is a cross-sectional descriptive-analytical study which is carried out in Larestan. The study population consists of those people who are infected by 'Cutaneous Leishmaniasis' during 2007 to 2017 and are referred to health care centers. The methodology and data collection are done based on the recorded information. Results: Among 4,965 'Cutaneous Leishmaniasis' infected patients who referred to health care centers of Larestan, 2407 patients (48.47%) are males and 2558 patients (51.53%) are females. In the ten-year time period of the study, 1,315 (26.6%) were infected to 'Cutaneous Leishmaniasis' in 2010. The maximum infected group consisted of 1,303 patients ranging from 0-5 years old, and the minimum infected group consisted of 90 patients ranging from 55-60 years old. Discussion: This study showed that female subjects were more polluted in Larestan city. There is also a significant relationship between age and 'cutaneous leishmaniasis'. Finally, it was found that the disease in the city of Larestan has been decreasing.